Has Authorship in the Decolonizing Global Health Movement Been Colonized? - Chris A. Rees; Gouri Rajesh; Hussein K. Manji; Catherine Shari; Rodrick Kisenge; Elizabeth M. Keating; Ikechukwu U. Ogbuanu; Kitiezo Aggrey Igunza; Richard Omore; Karim P. Manji (Ubiquity Press, 2023)
Background: Decolonization in global health is a recent movement aimed at relinquishing remnants of supremacist mindsets, inequitable structures, and power differentials in global health. Objective: To determine the author demographics of publications on decolonizing global health and global health partnerships between low- and middle-income countries (LMICs) and high-income countries (HICs). Methods: We conducted a cross-sectional analysis of publications related to decolonizing global health and global health partnerships from the inception of the selected journal databases (i.e., Medline, CAB Global Health, EMBASE, CINAHL, and Web of Science) to November 14, 2022. Author country affiliations were assigned as listed in each publication. Author gender was assigned using author first name and the software genderize.io. Descriptive statistics were used for author country income bracket, gender, and distribution. Findings: Among 197 publications on decolonizing global health and global health partnerships, there were 691 total authors (median 2 authors per publication, interquartile range 1, 4). Publications with author bylines comprised exclusively of authors affiliated with HICs were most common (70.0%, n = 138) followed by those with authors affiliated both with HICs and LMICs (22.3%, n = 44). Only 7.6% (n = 15) of publications had author bylines comprised exclusively of authors affiliated with LMICs. Over half (54.0%, n = 373) of the included authors had names that were female and female authors affiliated with HICs most commonly occupied first author positions (51.8%, n = 102). Conclusions: Authors in publications on decolonizing global health and global health partnerships have largely been comprised of individuals affiliated with HICs. There was a marked paucity of publications with authors affiliated with LMICs, whose voices provide context and crucial insight into the needs of the decolonizing global health movement.